ENVIRONMENTAL PRAYER MEANING FOR THE CATHOLIC COMMUNITY IN NGESTI RAHAYU VILLAGE, PUNGGUR, CENTRAL LAMPUNG, LAMPUNG - Darma Nur Yadi; Ahmad Muttaqin; Luthfi Salim (UIN Sunan Kalijaga Yogyakarta, 2026)
The lack of academic studies specifically examining the meaning of environmental prayer for rural Catholic communities living as minorities indicates a research gap, particularly in understanding the spiritual, social, and existential dimensions of prayer at the grassroots community level. This study aims to reveal the meaning of environmental prayer for the Catholic community in Ngesti Rahayu Village, Central Lampung, based on the life experiences and religious awareness of the people. This study employs a qualitative method using Edmund Husserl’s phenomenological approach to explore the religious experiences of the faithful as lived within their lifeworld, supplemented by a theological approach to interpret the field findings in light of Catholic Church teachings. Data were collected through in-depth interviews, observation, and documentary analysis, then analyzed through the stages of reduction, data presentation, and drawing conclusions. The results of the study show that environmental prayer is interpreted by the faithful in three main aspects: religious meaning as a space for encountering God and strengthening faith identity; social meaning as a means of building brotherhood, solidarity, and social capital within the community; and existential meaning as a source of inner peace, hope, and resilience in facing life’s challenges. These findings confirm that environmental prayer not only functions as a ritual practice but also plays an important role in shaping the communal spirituality and social cohesion of rural Catholics in a pluralistic society. Keywords: Environmental Prayer; Catholic Community; Communal Spirituality Abstrak Minimnya kajian akademik yang secara khusus mengkaji pemaknaan doa lingkungan bagi komunitas umat Katolik di pedesaan yang hidup sebagai minoritas menunjukkan adanya celah penelitian, terutama dalam memahami dimensi spiritual, sosial, dan eksistensial doa pada tingkat komunitas basis. Penelitian ini bertujuan untuk mengungkap makna doa lingkungan bagi komunitas umat Katolik di Desa Ngesti Rahayu, Lampung Tengah, berdasarkan pengalaman hidup dan kesadaran religius umat. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi Edmund Husserl untuk menggali pengalaman religius umat sebagaimana dialami dalam dunia kehidupan mereka, serta diperkaya dengan pendekatan teologis guna menafsirkan temuan lapangan dalam terang ajaran Gereja Katolik. Data diperoleh melalui wawancara mendalam, observasi, dan studi dokumentasi, kemudian dianalisis melalui tahapan reduksi, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa doa lingkungan dimaknai umat dalam tiga aspek utama: makna religius sebagai ruang perjumpaan dengan Allah dan penguatan identitas iman; makna sosial sebagai sarana membangun persaudaraan, solidaritas, dan modal sosial komunitas; serta makna eksistensial sebagai sumber ketenangan batin, harapan, dan ketahanan dalam menghadapi persoalan hidup. Temuan ini menegaskan bahwa doa lingkungan tidak hanya berfungsi sebagai praktik ritual, tetapi juga berperan penting dalam pembentukan spiritualitas komunal dan kohesi sosial umat Katolik pedesaan di tengah masyarakat majemuk. Kata kunci: Doa Lingkungan; Pengalaman Umat; Spiritualitas Komunal